Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/jp305403r
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Engineering of Graphene Oxide Nanosheets

Abstract: Many unique properties of graphene oxide (GO) strongly depend on the oxygenated functional groups and morphologies. Here, the photoreaction process is demonstrated to be very useful to control these factors. We report the fast, simple production of nanopores in porous GO via photoreaction in O2 under UV irradiation at room temperature. Quantitative analysis using X-ray photoelectron spectroscopy showed that nanopores were produced in areas of oxygenated groups (sp3 carbon bonds), creating porous reduced graphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 35 publications
2
79
1
Order By: Relevance
“…The first step was the synthesis of graphene oxide (GO) which was done using a modified Hummer's Method as reported by Koinuma et al [13]. To produce one batch of GO, four grams of graphite powder and four grams of sodium nitrate were dissolved in 184 mL of concentrated sulfuric acid in a 2-L beaker under an ice bath with vigorous stirring using a magnetic stirrer for 30 minutes.…”
Section: Synthesis Of Graphenementioning
confidence: 99%
“…The first step was the synthesis of graphene oxide (GO) which was done using a modified Hummer's Method as reported by Koinuma et al [13]. To produce one batch of GO, four grams of graphite powder and four grams of sodium nitrate were dissolved in 184 mL of concentrated sulfuric acid in a 2-L beaker under an ice bath with vigorous stirring using a magnetic stirrer for 30 minutes.…”
Section: Synthesis Of Graphenementioning
confidence: 99%
“…34 Therefore, incorporation of GO into membrane has been applied to enhance the water permeation and anti-fouling of membrane. 35,36 For instance, Zhang et al 37 prepared the high anti-fouling polyvinylidene uoride (PVDF) UF membranes via blending GO into the matrix membrane. In order to suppress the membrane fouling, Lee et al 38 regulated the structure and surface charge of polysulfone (Psf) UF membrane by incorporating GO nano-materials.…”
Section: -31mentioning
confidence: 99%
“…Emadzadeh et al investigated the addition of different loadings of titanium dioxide (TiO 2 ) nanoparticles in the polysulfone (PSf) substrate of a TFC membrane, and the results revealed that both the hydrophilicity and porosity of the substrate were increased with the addition of TiO 2 [18,19]. More recently, the incorporation of GO in various membrane types for water treatment to improve their performance, in particularly their anti-fouling properties, has attracted considerable attention [7,20]. For instance, the addition of GO in poly(vinylidene fluoride) (PVDF) ultrafiltration (UF) membrane to improve water flux and anti-fouling properties [21], the incorporation of GO in PSf UF membrane to manipulate the micro-structure and surface charge of the membrane, thus suppressing the fouling behavior [22].…”
Section: Introductionmentioning
confidence: 99%